Practical Aspects of Academic Literacy Development in Higher Education Institutions - N. V. Ageenko; S. G. Menshenina; V. V. Dobrova; P. G. Labzina (Moscow Polytechnic University, 2021)
Global tendencies in all scientific spheres require developed academic literacy of the researcher for effective international communication. Foreign language communication in a professional academic environment implies proficiency in the language of academic discourse. For academic discourse, as a component of academic literacy, development of academic writing skills is crucial. Higher educational institutions realize the necessity to design academic writing courses, and determine their place in the curriculum. Following the challenges of the time and academic community demands, SSTU English Language instructors designed an academic writing course to increase the methodological and academic literacy of students and young researchers. We believe that the development of the key educational and communicative foreign language competencies for academic and professional interaction can contribute to successful integration into the international scientific environment. Course design considered foreign experience, methods and curricula in the field of academic writing and academic reading.